Golden handshakes: Separation pay for retired and dismissed CEOs - Yermack, David (Journal of Accounting and Economics, 2006)
This paper studies separation payments made when CEOs leave their firms. In a sample of 179 exiting Fortune 500 CEOs, more than half receive severance pay and the mean separation package is worth $5.4 million. The large majority of severance pay is awarded on a discretionary basis by the board of directors and not according to terms of an employment agreement. For the subset of exiting CEOs who are dismissed, separation pay generally conforms to theories related to bonding and damage control. Shareholders react negatively when separation agreements are disclosed, but only in cases of voluntary CEO turnover.